Efisiensi Tiang Group Konfigurasi 2x2 Fondasi Helical Pile pada Tanah Gambut - Fadlan Fadlan; Ferry Fatnanta; Muhardi Muhardi (Jurnal Ilmiah Universitas Batanghari Jambi, 2019)
Installation of helical pile foundations in different formations and distances will provide different bearing capacities in peat soils. For this reason, a correction value to the bearing capacity of the pile group is required, which is stated with efficiency. This paper aims to analyze the bearing capacity of the helical pile group configuration 2x2 with variations in the distance between the piles of 1.5D, 2.0D, 2.5D, & 3.0D on peat soils, as well as obtaining the efficiency values from the bearing capacity and from the Converse–Laberre formula. The analysis shows the efficiency of the pile for the distance between the 1.5D pile is 0.99, the distance of 2.0 D is 0.93, the distance of 2.5D is 0.86, and the distance of 3.0D is 0.79. The efficiency obtained from the Converse-Laberre formula for a distance of 1.5D is 0.44, a distance of 2.0D is 0.56, a distance of 2.5D is 0.64 and a distance of 3.0D is 0.70.